Intrinsic Factors of Mortality Due to DHF in 2018-2021 - Cahyati, Widya Hary; Setiawan, Andreas Wilson; Maharani, Chatila (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
The number of cases of mortality due to dengue fever in the ex-residence of Semarang and ex-residence of Pati from January to December 2020 was 24 people. The purpose of this study was to analyze the factors associated with mortality from dengue fever from 2018-2020 in ex-residents of Semarang and ex-residents of Pati. This type of quantitative analytic research with a case-control approach. The sample consisted of 60 respondents, 30 case groups, and 30 control groups, taken using the Consecutive sampling technique. Analysis using chi-square test. The results showed that the related factors were gender (p-value = 0.009, OR = 4.750) and a history of suffering from DHF (p-value = 0.001, OR 7.500). Lack of public awareness of the importance of 3M in preventing DHF. It is necessary to conduct counseling with promotional media that is more interesting and informative to the surrounding community so that they care about the surrounding environment, so that the community can start by cooperate in cleaning the environment.